Query answering in ontologies under preference rankings - Ceylan, İ; Lukasiewicz, T; Peñaloza, R; Tifrea-Marciuska, O (AAAI Press/International Joint Conferences on Artificial Intelligence, 2017)
We present an ontological framework, based on preference rankings, that allows users to express their preferences between the knowledge explicitly available in the ontology. Using this formalism, the answers for a given query to an ontology can be ranked by preference, allowing users to retrieve the most preferred answers only. We provide a host of complexity results for the main computational tasks in this framework, for the general case, and for EL and DL-Litecore as underlying ontology languages.